The art of good neighboring in Kampoeng Cyber: Community economic development through ICTs. Issue 5 (20th October 2019) - Khoir, Safirotu; Davison, Robert M.
ABSTRACT: In this exploratory paper, we examine how a community in Indonesia, Kampoeng Cyber, leverages Information & Communication Technologies (ICTs) to support its social and community development. We describe the various technology-related activities and their impact on the transformation of the community that led to improvements in the quality of life of the community members. We interviewed thirteen of the community members and made direct observations of the community, its website, and social media accounts used by the community members. Textual analysis of the data revealed that the ICTs play a significant role in helping the community members to develop themselves in terms of both economic development and social tie maintenance. Our results suggest that government policies dealing with urban development may need to have a more explicit focus related to ICT use and community empowerment. We contribute to an enhanced understanding of ICT-based initiatives that strengthen the local community through participation.